2009
DOI: 10.1111/j.1742-7843.2008.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Gln27→Gluβ2‐Adrenergic Receptor Polymorphism in Heart Failure Patients: Differential Clinical and Oxidative Response to Carvedilol

Abstract: Abstract:We investigated the clinical response of chronic heart failure patients with β 2 -adrenergic receptor Gln 27 → Glu polymorphism treated for 6 months with carvedilol, a α / β -antagonist with antioxidant properties. The 6-min. walk test, the left ventricular ejection fraction, heart rate, plasma norepinephrine and malondialdehyde, a stress oxidative marker, concentrations were evaluated at baseline and after treatment for 6 months with carvedilol in 33 stable chronic heart failure patients with the Gln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Полиморфизмы адренергических рецепто-ров (генетические аберрации в генах β1-, β2-и α2с-адренергичесих рецепторов (АР)) сопря-жены с различной выраженности ответом па-циентов на терапию β-адреноблокаторами [9][10][11]. Описанные факты должны быть приняты во внимание, несмотря на то, что большин- ство результатов были получены посред-ством ретроспективных анализов и в совокуп-ности не представляют достаточную доказа-тельную базу для того, чтобы лечь в основу рекомендаций по терапии, базирующейся на генетическом тестировании.…”
Section: ~ 47 ~unclassified
See 2 more Smart Citations
“…Полиморфизмы адренергических рецепто-ров (генетические аберрации в генах β1-, β2-и α2с-адренергичесих рецепторов (АР)) сопря-жены с различной выраженности ответом па-циентов на терапию β-адреноблокаторами [9][10][11]. Описанные факты должны быть приняты во внимание, несмотря на то, что большин- ство результатов были получены посред-ством ретроспективных анализов и в совокуп-ности не представляют достаточную доказа-тельную базу для того, чтобы лечь в основу рекомендаций по терапии, базирующейся на генетическом тестировании.…”
Section: ~ 47 ~unclassified
“…Так наличие аллеля Gly49 связано с более благоприятным прогнозом и снижением риска смертности у больных с ХСН [10]. Полиморфизм Arg389Gly (1165G → C) гена β1-АР представляет особый инте-рес, так как мутация затрагивает область, от-ветственную за связывание с G-белком (внут-риклеточный карбокситерминальный сайт).…”
Section: ~ 47 ~unclassified
See 1 more Smart Citation
“…Clinical studies have generally failed to demonstrate an association of response with Gly16Arg genotype [87]. On the other hand, several studies found that Glu27 genotype was associated with better b-blocker response in terms of HR, and LVEF changes [88]. Moreover, possessing ADRB1 Arg389 and ADRB2 Gln27 variant genotypes together was associated with twofold increase in mortality compared to other genotype groups in patients treated with carvedilol.…”
Section: Adrb2mentioning
confidence: 99%
“…Las variantes del receptor ß2-adrenérgico se han estudiado intensamente por su acción en la regulación de la contractilidad y ritmo cardíaco. Entre los polimorfismos dentro de la región codificante del gen de este receptor, se ha descrito que el polimorfismo Gln27 Glu tiene un impacto funcional en los pacientes con insuficiencia cardíaca, los que al ser tratados con carvedilol mostraron una significativa mejoría en su función cardíaca 3 .…”
unclassified